Pengembangan Model Produksi Eco-Enzyme Berbasis Limbah Dapur Hotel sebagai Strategi Operasional Berkelanjutan di Ts Suites Seminyak Bali - I Made Yuda Adnyana; I Nyoman Sedeng; Putu Sabda Jayendra (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to develop a hotel kitchen waste-based Eco-enzyme production model as a sustainable operational strategy at TS Suites Seminyak Bali. The study used a descriptive qualitative approach with an applied case study design. Data were collected through in-depth interviews, field observation, documentation, and review of operational documents. Informants were selected purposively from management, kitchen, stewarding, food and beverage, housekeeping public area, engineering, purchasing or cost control, human resources, and related operational units. The data were analyzed thematically through data reduction, data display, conclusion drawing, and verification. Data credibility was strengthened through source, technique, and document triangulation. The findings show that the hotel already has a basic flow for collecting and sorting kitchen waste, but it is not yet supported by a specific SOP, consistent organic waste volume records, and cross-department monitoring. The developed model consists of seven main components: sorting suitable organic materials, applying the formula of 3 kg fruit and vegetable waste : 1 liter molasses : 10 liters water, assigning a person in charge, providing a safe fermentation area, using a production logbook, testing limited operational use, and conducting periodic evaluation. The study concludes that Eco-enzyme can strengthen green operation, circular economy principles, and the palemahan value of Tri Hita Karana when applied through clear SOPs, training, supervision, and controlled areas of use.